Don’t Let It Get Under Your Skin! – Vaccination Protects the Skin Barrier of Common Carp From Disruption Caused by Cyprinid Herpesvirus 3 - Adamek, Mikolaj; Matras, Marek; Rebl, Alexander; Stachnik, Magdalena; Falco, Alberto; Bauer, Julia; Miebach, Anne-Carina; Teitge, Felix; Jung-Schroers, Verena; Abdullah, Muhammad; Krebs, Torben; Schröder, Lars; et al. (Frontiers in Immunology, 2022)
Vaccination is the best form of protecting fish against viral diseases when the pathogen cannot be contained by biosecurity measures. Vaccines based on live attenuated viruses seem to be most effective for vaccination against challenging pathogens like Cyprinid herpesvirus 3. However, there are still knowledge gaps how these vaccines effectively protect fish from the deadly disease caused by the epitheliotropic CyHV-3, and which aspects of non-direct protection of skin or gill integrity and function are important in the aquatic environment. To elucidate some elements of protection, common carp were vaccinated against CyHV-3 using a double deletion vaccine virus KHV-T ΔDUT/TK in the absence or presence of a mix of common carp beta-defensins 1, 2 and 3 as an adjuvants. Vaccination induced marginal clinical signs, low virus load and a minor upregulation of cd4, cd8 and igm gene expression in vaccinated fish, while neutralisation activity of blood serum rose from 14 days post vaccination (dpv). A challenge infection with CyHV-3 induced a severe disease with 80-100% mortality in non-vaccinated carp, while in vaccinated carp, no mortality was recorded and the virus load was >1,000-fold lower in the skin, gill and kidney. Histological analysis showed strongest pathological changes in the skin, with a complete destruction of the epidermis in non-vaccinated carp. In the skin of non-vaccinated fish, T and B cell responses were severely downregulated, inflammation and stress responses were increased upon challenge, whereas vaccinated fish had boosted neutrophil, T and B cell responses. A disruption of skin barrier elements (tight and adherence junction, desmosomes, mucins) led to an uncontrolled increase in skin bacteria load which most likely exacerbated the inflammation and the pathology. Using a live attenuated virus vaccine, we were able to show that increased neutrophil, T and B cell responses provide protection from CyHV-3 infection and lead to preservation of skin integrity, which supports successful protection against additional pathogens in the aquatic environment which foster disease development in non-vaccinated carp.